Audit Sistem Informasi Pada Tata Usaha Dengan Menggunakan Cobit 4.1 Domain Delivery And Suport (Ds) Pada Sd N 7 Belida Darat - Altera, Altera Iyan Rani (Jurnal Pengembangan Sistem Informasi dan Informatika, 2025)
systems and technology have become very important components for the success of businesses and organizations where information systems and technology can help all types of businesses improve the efficiency and effectiveness of business processes, managerial decision-making making, and teamwork so that they can strengthen business and organizational competitiveness quickly and efficiently, easy, Management of academic information systems that are not managed properly will have an impact on the low quality of service, low satisfaction with IT user. So that it can affect the level of stakeholder trust in educational institutions。 With the implementation of COBIT 4.1, it is expected to improve all the shortcomings and weaknesses of the current system for the better. Under the objectives, Cobit is a collection of best practice documentation for IT governance that can help auditors, users, and management bridge the mix of business risk, control requirements, and technical issues. A case study of the Administrative Information System (SD Negeri 7 Belida Darat) was conducted in this study. As an agency in the field of education, we do a lot of processing administrative data such as student data, teacher data, class data, student lesson schedule data, student grade data, data recap of student attendance, curriculum data, and tuition payment data. The data is in large quantities, so storage and administration must be carried out properly. In processing school administration data, it aims to develop the quality of school administration and improve the work performance of school administrative staff in achieving the specified work results COBIT work